Implementation of Patient Safety Program in the Emergency Installation of H. Adam Malik General Hospital Medan - Siti Farisya Tsamarah Sembiring; Zulfendri Zulfendri; Siti Khadijah (RIRAI Publisher, 2023)
Patient Safety Program stipulated in the Minister of Health Regulation of the Republic of Indonesia No. 11 of 2017 namely Patient Safety Standards; Patient safety goals, and 7 steps towards patient safety. 8 Contributor Factors in Patient Safety are external factors, organization and management, physical environment, teamwork, officers, tasks, patients, and communication. This study uses qualitative research with a phenomenological approach by conducting in-depth interviews of several health workers at the Adam Malik Hospital Medan. Implementation of patient identification using 2 identities and is used for confirmation before the procedure, the implementation of effective communication is done by doing readback before carrying out the procedure, aware of high alert drugs by prescribing drugs into pharmacy, then drugs are formulated by pharmacy and before being given to patients with double checks, ensuring the accuracy of location, procedure and patients by site marking on body parts and signed in the medical recording, preventing the infection of medical Reducing the risk of patients falling by giving yellow bracelets and assistance to patients. In external contributors, the regulations used by Adam Malik Hospital are adapted from the Law of the Republic of Indonesia and the Regulation of the Minister of Health of the Republic of Indonesia, organizations and management support the staff in carrying out patient safety programs, the hospital environment is appropriate but there are several facilities that must be improved, the team's work has been running without difficulties. It patient information and educating patients.